Movement Patterns of Resident and Translocated Beavers at Multiple Spatiotemporal Scales in Desert Rivers - Doden, Emma; Budy, Phaedra; Avgar, Tal; Young, Julie K. (Frontiers in Conservation Science, 2022)
Wildlife translocations alter animal movement behavior, so identifying common movement patterns post-translocation will help set expectations about animal behavior in subsequent efforts. American and Eurasian beavers (Castor canadensis; C. fiber) are frequently translocated for reintroductions, to mitigate human-wildlife conflict, and as an ecosystem restoration tool. However, little is known about movement behavior of translocated beavers post-release, especially in desert rivers with patchy and dynamic resources. We identified space-use patterns of beaver movement behavior after translocation. We translocated and monitored nuisance American beavers in desert river restoration sites on the Price and San Rafael Rivers, Utah, USA, and compared their space use to resident beavers after tracking both across two years. Resident adult beavers were detected at a mean maximum distance of 0.86 ± 0.21 river kilometers (km; ±1 SE), while resident subadult (11.00 ± 4.24 km), translocated adult (19.69 ± 3.76 km), and translocated subadult (21.09 ± 5.54 km) beavers were detected at substantially greater maximum distances. Based on coarse-scale movement models, translocated and resident subadult beavers moved substantially farther from release sites and faster than resident adult beavers up to six months post-release. In contrast, fine-scale movement models using 5-minute location intervals showed similar median distance traveled between resident adult and translocated beavers. Our findings suggest day-to-day activities, such as foraging and resting, were largely unaltered by translocation, but translocated beavers exhibited coarse-scale movement behavior most similar to dispersal by resident subadults. Coarse-scale movement rates decreased with time since release, suggesting that translocated beavers adjusted to the novel environment over time and eventually settled into a home range similar to resident adult beavers. Understanding translocated beaver movement behavior in response to a novel desert system can help future beaver-assisted restoration efforts to identify appropriate release sites and strategies.